Inovasi Bahan Ajar Fisika Terapan Berbasis Scientific untuk Program Studi Teknologi Nautika - Erlinda, Nelfi; Yanti, Melda; Riyadi, Slamet; Lelfita, Lelfita (Universitas Negeri Padang, 2025)
This study aims to develop Applied Physics teaching materials based on a scientific approach to enhance students' creativity in the Nautical Technology Study Program at the Politeknik Pelayaran Sumatera Barat. Creativity, which includes critical thinking, flexibility, and originality, is an essential competence in science education to address the challenges of the workforce. This study employs the Research and Development (R&D) method with the ADDIE development model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. The results indicate that students previously lacked relevant printed teaching materials, and the learning process relied on digital resources like presentations, which were deemed less scientific. The developed teaching materials cover Statics, Motion Dynamics, Fluids, and Temperature, presented systematically and applicatively. Experts have confirmed that these teaching materials have high feasibility, with an average score of ≥3.26, although some revisions are needed to enhance the context and relevance of the content. Student responses to these teaching materials demonstrate high effectiveness in helping them understand Applied Physics concepts, with average scores for material and language aspects reaching ≥3.09, respectively. Moreover, the scientific activities in the teaching materials successfully encouraged students to think creatively and generate new ideas. In conclusion, the scientific-based Applied Physics teaching materials developed effectively enhance student creativity and are relevant to education and industry needs. This study significantly contributes to innovation in science teaching methods in higher education.